Переваги та недоліки цифровізації в банківській сфері. - Третякова, Олена Василівна; Харабара, Віолетта; Грешко, Роман Ігорович (My University, 2021)
The digitalization of the economy is considered as a modern global trend of economic and social development, which is based on the use of information and computer technologies (ICT) and digital technologies and leads to increased economic efficiency and quality of life. The advantages and disadvantages of digitalization in the banking sector are identified.
Keywords: банківська сфера; цифровізація; діджиталізація; банківські послуги; цифрова трансформація; цифрові технології; цифрова економіка